TINGKAT KETERAMPILAN TEKNIK DASAR PERMAINAN BOLA VOLI PADA SISWA PESERTA EKSTRAKURIKULER - Fauziah Rahmayanti Matondang; Dandi Dantri Lubis; Faisal Tahan Siagian; Rimbun Gustiadi Purba; Niko Purba; Fadlan Albi; Dewi Endriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the level of basic technical skills in volleyball among students participating in extracurricular activities. This is a quantitative descriptive study using a survey method with data collection techniques in the form of physical tests (battery test). The study sample consisted of 20 students selected using total sampling. The instruments used included four basic skill test items: the overhand/underhand serve test, the underhand pass test, the overhand pass test, and the smash test. Data analysis employed quantitative descriptive statistical analysis using percentages. The results of the study indicate that the level of basic volleyball skills among students participating in the extracurricular program is predominantly in the “Fair” category (50%), the “Good” category (25%), and the “Poor” category (25%). Based on these results, there is a need for a more intensive evaluation of the training program, particularly for the smash and serve techniques, which are still rated low.